A geometric morphometric evaluation on three populations of endemic species, Dorcadion micans (Cerambycidae, Coleoptera) in Ankara Province from Turkey with a new subspecies description - Okutaner, Atilay Yağmur; Sarikaya, Asli Doğan; Sarikaya, Özkan; Özdikmen, Hüseyin (Zootaxa, 2021)
Due to some biological features, species belonging to genus Dorcadion Dalman, 1817 (Coleoptera: Cerambycidae) can be easily divided into isolated populations. This can be considered as an important factor of speciation process and allows the observation of various effects of biological evolution of taxa. These effects can be measured on morphological characters with some different approaches such as geometric morphometrics. This study aims to determine pronotum and elytra shape differences of the samples of three isolated localities of Turkey (Akyurt, Bala, and Beynam) detected in Ankara, and to contribute to taxonomic and evolutionary knowledge of Dorcadion micans Thomson (1867) by evaluating the analysis of outcomes. As a result, significant differences between populations were detected both in pronotum and elytra. Besides, common variations were observed in some morphological characters of the Bala and Beynam populations, unlike Akyurt population. Accordingly, the distinguishing characters are discussed, and the following new subspecies is described: Dorcadion micans majoripunctum ssp. nov. from Ankara province in Northern part of Central Anatolia.